Help-Seeking Attitude of Nigerian Undergraduates Toward Mental Health Issues - Muhammed, Shuaib Abolakale; Akinduyo, Tosin Emmanuel; Adebayo, Habeebat Olaitan; Mabaso, Nancy Phyllis Makhosazane (Bulletin of Counseling and Psychotherapy, 2024)
This study investigated the help-seeking attitude of undergraduates at the University of Ilorin Nigeria toward mental health issues. The study employed a descriptive survey design. A multistage sampling method was used in selecting a total of 400 participants. The demographic data and research questions were examined using percentage distribution. The hypotheses were tested using t-tests and Analysis of Variance (ANOVA) statistical methods at a significance level of 0. 05. The help-seeking attitude of respondents towards mental health difficulties did not vary significantly based on gender. However, there were substantial differences depending on age, degree of study, and students' place of residence. The vast majority of undergraduates rather talk to friends and family about their mental health problems than seek psychotherapy or medical help. School counsellors need to educate students on the significance of seeking help from trained mental health professionals.